POSTER| Address2vec: Generating Vector Embeddings for Blockchain Analytics - Hussein, Ali; Nalwooga, Samiiha (My University, 2019)
Bitcoin Blockchain is a completely public open currency transaction ledger, recent growth in the crypto-currency market has driven many lawful and blackmarket actors using Bitcoin as the main method of payment. I propose address2vec an algorithm to generate vector representations of addresses on the Bitcoin Blockchain. I am able to present better results than a baseline random approach in predicting hoarding vs spending behaviour. The current work allows for utilization of common machine learning algorithms on bitcoin transaction addresses.
Keywords: graph embeddings; node2vec; representation learning; word2vec